Efficacy and safety of golimumab as add-on therapy to disease-modifying antirheumatic drugs: results of the GO-MORE study. Issue 8 (5th June 2013) - Combe, Bernard; Dasgupta, Bhaskar; Louw, Ingrid; Pal, Sarvajeet; Wollenhaupt, Jürgen; Zerbini, Cristiano A F; Beaulieu, Andre D; Schulze-Koops, Hendrik; Durez, Patrick; Yao, Ruji; Vastesaeger, Nathan; Weng, Haoling H; et al.
Abstract : Objectives: To evaluate the efficacy and safety of subcutaneous golimumab as add-on therapy in patients with active rheumatoid arthritis (RA) despite disease-modifying antirheumatic drug (DMARD) treatment. To evaluate an intravenous plus subcutaneous (IV+SC) golimumab strategy in patients who had not attained remission. Methods: GO-MORE was an open-label, multinational, prospective study in patients with active RA in typical clinical practice settings. In part 1, patients received add-on monthly 50-mg subcutaneous golimumab for 6 months. The percentage of patients with good/moderate European League Against Rheumatism (EULAR) 28-joint disease activity score (DAS28)–erythrocyte sedimentation rate (ESR) response was compared in patient subgroups with various concurrent or previous DMARD treatments. In part 2, patients with EULAR responses but not remission were randomly assigned to receive IV+SC or subcutaneous golimumab to month 12; DAS28–ESR remission was measured. Results: 3366 patients were enrolled. At baseline of part 1, 3280 efficacy-evaluable patients had mean disease duration of 7.6 years and mean DAS28–ESR of 5.97 (SD=1.095). At month 6, 82.1% achieved good/moderate EULAR responses and 23.9% attained remission. When EULAR responses were analysed by the number of previously failed DMARD or the concomitant methotrexate dose, DMARD type, or corticosteroid use, no statistically significant differences were observed. Part 2 patients (N=490) who received IV+SC or subcutaneous golimumab achieved similar remission rates (∼25%). Adverse events were consistent with previous reports of golimumab and other tumour necrosis antagonists in this population. Conclusions: Add-on monthly subcutaneous golimumab resulted in good/moderate EULAR response in most patients; 25% achieved remission after 6 more months of golimumab, but an IV+SC regimen provided no additional efficacy over the subcutaneous regimen.